Preventing white spot lesions around orthodontic brackets: efficacy of pre-reacted glass-ionomer barrier coat versus silver diamine fluoride: an in vitro study - Enas A. Elshenawy; Safa B. Alawy; Wafaa Yahia Alghonemy; Ahmed Ibrahime El dosoky (BDJ Open)
Abstract Objectives to compare the effect of using a pre-reacted glass-ionomer (PRG) barrier coat versus silver diamine fluoride (SDF) varnish treatment before orthodontic bracket bonding to prevent white spot lesions (WSL). The effect of these materials on the shear bond strength of orthodontic brackets was evaluated through an in vitro study. Methods One hundred-five premolars were used; forty-two specimens were designated for comparing SDF versus PRG-barrier coat using a scanning electron microscope (SEM) with elemental analysis and microhardness testing (n = 21/group). Tested materials were applied in a split-tooth design protocol (side A: control, side B: treated). Measurement was made at baseline and after bracket placement and exposure to the pH cycle. A polarized light microscope (PLM) was used for qualitative examination. Sixty-three specimens were intended for shear bond strength (SBS) testing after the pH cycle as follows: control group (no treatment), SDF group, and PRG-barrier coat group (n = 21/group). Statistical analysis was done using Paired T-test. Results SEM for specimens treated by SDF or PRG revealed enamel remineralization with calcium deposits and small porosities between the crystallites. All groups had a significant difference regarding the Ca/P ratio and microhardness. Baseline hardness for both groups was significantly higher than the treated sides, which was significantly higher than the non-treated sides (P = 0.000*) and (P = 0.000*) in accordance with the Paired T-test. In comparing SDF with PRG-coat groups, the T-test showed non-significant differences in mean differences between treated and baseline hardness values (T = 0.32, P = 0.74). PLM for treated specimens by SDF or PRG depicted an evident remineralized surface enamel layer. SBS values did not differ significantly between groups. Conclusions As confirmed by SEM and PLM, applying either SDF varnish or PRG-barrier coat before bonding orthodontic brackets could effectively prevent the development of WSL and achieve surface enamel protection. In addition, the two applied varnishes showed slightly higher shear bond strength of orthodontic brackets compared to the control group, with the SDF slightly higher than PRG. Also, clinical translation is needed in future research to evaluate the study.